History education and changing epistemic beliefs about history: An intervention in initial teacher training - Diego Miguel-Revilla; María Sánchez-Agustí; Teresa Carril-Merino (South African Journal of Education)
Epistemic beliefs can have an important effect on teaching practices determining how teachers approach a discipline in the classroom in different contexts. The research reported on here focused on initial teacher education, assessing the pre-service social studies teachers’ epistemic beliefs about history, and their ideas regarding history education. We examined the way in which the beliefs of 59 Spanish participants had evolved after an intervention focused the fostering of historical thinking and understanding. A pre-test-post-test quasi-experimental design was applied, using the Beliefs about History Questionnaire (BHQ), which was supplemented by a qualitative approach. Results indicate progression, although it was more noticeable in pre-service primary education teachers who adhered to a more nuanced vision about historical knowledge and both objectivity and subjectivity. The way that participants with different conceptions about history thought about educational aspects were also examined and discussed. Findings suggest the effectiveness of educational interventions in initial teacher training to allow pre-service teachers to understand the specificity of this discipline.